Role of the general surgeon in the traumatized cranioencephalic - Ríos Bruno, Guaymirán (Cirugía del Uruguay, 1975)
The cases of three patients with extradural hematomas who died because of delay in surgery, are presented. In two cases this was due to the passive attitude of the general surgeon on duty, whose only gesture was to order the transfer of the. patient to a Neurosurgical Center. In the third case, the concern , ;:,o,n1 in wanting to localize with exactitude the heatoma by means of an angiographical study caused g:-ea· delay, in the presence of clear clinical evidence, -nich demanded urgent decompression. The author mentions the increasing frequency of :hese cases since the specialized Neurosurgical Centers were created. He argue for a more :¡ctive róle for the general surgeon in the management of this injuries and describes the basical technical principies that must be followed.